An advanced hybrid algorithm for nonlinear function optimization with real world applications. (12th August 2021) - Verma, Pooja; Parouha, Raghav Prasad
Summary: This article presents an advanced hybrid algorithm ( h aDEPSO) for nonlinear constrained function optimization problem. It consists of the advised advanced differential evolution, that is, aDE (wherein a novel mutation, crossover, and selection strategy is introduced, to avoid premature convergence) and particle swarm optimization, namely, aPSO (in which novel gradually varying parameters is utilized, to escape stagnation). The proposed h aDEPSO achieve better results as aDE and aPSO provides diverse convergence characteristic to the solution space. Moreover, in h aDEPSO distinct population is merged with other in a predefined way, to balance between exploration and exploitation. Efficiency of the proposed hybrid h aDEPSO along with its integrating component aDE and aPSO are inspected on IEEE CEC'2006 constrained benchmark functions and IEEE CEC'2011 real world problems. According to the comparison results, the proposed methods achieved better results than traditional DE and PSO with their hybrids as well as over many state‐of‐the‐art algorithms.